2015
DOI: 10.3126/ijasbt.v3i1.11847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Dates on the Yield and Quality of True Seeds of Onion

Abstract: The present study was stimulated by the problem of onion seed production where seed production is possibly only winter period after whichrapid increase in temperature as well as early shower adversely affect the quality of seed. To overcome this situation a field experiment wasundertaken to find out the optimum planting time for maximizing quality true seeds of onion. The experiment was laid out in a randomizedcomplete block design with four replications. The treatments were five planting dates viz. 1 October,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 1 publication
2
14
1
2
Order By: Relevance
“…Planting time significantly influenced (p ≤ 0.01) number of seeds per umbel which ranged from 47.4 to 533.3 seeds per umbel with an average of 214.0. In the earlier studies, number of seeds per umbel (256.6-515.3) and (93.0-299.9) were reported in Ethiopia (Kobo area) and Bangladesh, respectively [5,8]. However, in the present study, the highest number of seeds per umbel (533.3) was recorded from September 1st planting date.…”
Section: Table 2 Effect Of Planting Time On Growth and Phonological Pcontrasting
confidence: 53%
See 3 more Smart Citations
“…Planting time significantly influenced (p ≤ 0.01) number of seeds per umbel which ranged from 47.4 to 533.3 seeds per umbel with an average of 214.0. In the earlier studies, number of seeds per umbel (256.6-515.3) and (93.0-299.9) were reported in Ethiopia (Kobo area) and Bangladesh, respectively [5,8]. However, in the present study, the highest number of seeds per umbel (533.3) was recorded from September 1st planting date.…”
Section: Table 2 Effect Of Planting Time On Growth and Phonological Pcontrasting
confidence: 53%
“…In this study, bulbs planted in September were longer and with more number of leaves compared to those planted in November. On the other hand, other study indicated that bulb planted in November was longer and with more number of leaves per plant compared to those planted in October [5]. This could be attributed to climatic variation among the study sites.…”
Section: Growth and Phonological Parametersmentioning
confidence: 70%
See 2 more Smart Citations
“…Perlakuan vernalisasi juga menunjukkan persen berbunga tanaman yang lebih besar (70.37-79.63%) dibandingkan tanaman yang tidak divernalisasi (29.63%). Sejalan dengan penelitian Mollah et al (2015), bahwa perlakuan tanpa vernalisasi menyebabkan jumlah umbel, diameter umbel bawang menjadi lebih rendah dibandingkan bawang yang diperlakuan dengan vernalisasi 10-15 0 C. Perbedaan stadia tumbuh menyebabkan perbedaan toleransi terhadap lingkungan, sehingga tanaman harus meregulasi proses pertumbuhan dan perkembangannya (Auge et al, 2017). Kemampuan berbunga dipengaruhi berbagai faktor lingkungan dan faktor genetik tanaman (Yang et al, 2016).…”
Section: Hasil Dan Pembahasanunclassified